Impact of PHITS spallation models on the neutronics design of an accelerator-driven system. Issue 10 (2nd October 2016) - Iwamoto, Hiroki; Nishihara, Kenji; Iwamoto, Yosuke; Hashimoto, Shintaro; Matsuda, Norihiro; Sato, Tatsuhiko; Harada, Masahide; Maekawa, Fujio
ABSTRACT: The impact of different spallation models and parametrisation of nucleon–nucleus interactions in the particle transport code PHITS on the nuclear characteristics of an accelerator-driven system (ADS) is investigated. Cut-off neutrons below 20 MeV calculated using the default option of the current spallation model (i.e. Liège intranuclear cascade (INC) model version 4.6, INCL4.6) are found to be 14% less than those calculated by the old spallation model (i.e. Bertini INC model). This decrease increases the proton beam current that drives the 800-MW thermal power and impacts various ADS parameters, including material damage, nuclear heating of the proton beam window and the inventory of spallation products. To validate these options based on the ADS neutronics design, we conduct benchmark calculations of the total and non-elastic cross sections, thick target neutron yields and activation reaction rate distributions. The results suggest that Pearlstein–Niita systematics, which is a default option of the nucleon–nucleus interaction parametrisation, would be the best option and that Bertini INC is better suited for cut-off neutrons than INCL4.6. However, because of the difficulty in making a definite conclusion on the spallation models, we conclude that relatively large uncertainty in the cut-off neutrons, which is the difference between the two spallation models (i.e. 14%), should be considered.